The politics of social conflict : the Peak Country, 1520-1770 - Wood, Andy (Cambridge studies in early modern British history., 1999)
This book provides a new approach to the history of social conflict, popular politics and plebeian culture in the early modern period. Based on a close study of the Peak Country of Derbyshire c. 1520-1770, it has implications for understandings of class identity, popular culture, riot, custom and social relations. A detailed reconstruction of economic and social change within the region is followed by an in-depth examination of the changing cultural meanings of custom, gender, locality, skill, literacy, orality and magic. The local history of social conflict sheds new light upon the nature of political engagement and the origins of early capitalism. Important insights are offered into early modern social and gender identities, civil war allegiances, the appeal of radical ideas and the making of the English working class. Above all, the book challenges the claim that early modern England was a hierarchical, 'pre-class' society. Second Prize in the Whitfield Prize 1999.